Long-term risk of malignancies in persons with ischemic heart disease treated with trimetazidine dihydrochloride - Yuen-Ting Cheng; Chun-Fung Sin; Edmond S. K. Ma; Stephen T. S. Lam; Shiu-Lun Au Yeung; Bernard M. Y. Cheung; Hung-Fat Tse; Kai-Hang Yiu; Yap-Hang Chan (Communications Medicine)
Abstract Background Metabolic reprogramming of energy processes is a cellular hallmark of various cancers. Whether trimetazidine, an anti-ischemic agent that preferentially potentiates cellular glucose oxidation, alters the long-term risk of malignancies is unknown. Methods In this multi-center, retrospective cohort study, we studied the effect of trimetazidine on new-onset malignancies in 200,563 ischemic heart disease patients (mean age 70.8 years, 46.6% female) using the Hong Kong Clinical Data Analysis and Reporting System (CDARS), comparing trimetazidine users (n = 16,873) to nitrate users (n = 183,690, as control) over at least 30 days. The primary endpoint was defined as the estimated effect of trimetazidine on the overall new-onset occurrence of any malignancies a priori specified, diagnosed 90 days or more after the cohort entry. Results Over a mean follow-up duration of 8.36 (6.42) years, the incidence rate of new-onset malignancies amongst trimetazidine users is significantly lower compared to the non-users (8.76 vs 12.3 per 1000-person years, trimetazidine to control incidence ratio, 0.71). Trimetazidine use is associated with improved event-free survival from new-onset malignancies (Mean survival: 231 [0.53] versus 225 [0.21] months, Chi-square = 161, P < 0.001). Multivariable Cox regression demonstrates an independently lower risk of new-onset malignancies associated with trimetazidine use, with (adjusted HRs, 0.71, 95% CI, 0.66–0.77, P < 0.001) and without (adjusted HRs, 0.71, 95% CI, 0.68–0.75, P < 0.001) propensity score matching. Subgroup analyses of new-onset malignancies including lung, colorectal, hepatobiliary & pancreatic, breast, stomach & oesophageal, renal & genito-urinary, prostate, and hematological malignancies, show similar risk reductions. Conclusions Modulation of metabolic reprogramming may represent a new therapeutic target for cancer prevention.